Elderly Care During the Pandemic and Its Future Transformation - Macchioni, Elena; Prandini, Riccardo (Italian Sociological Review, 2022)
The research we are presenting is based on the following question: what happened inside the Residential Care Facilities and the nursing homes for the fragile and /or non-self-sufficient elderly, between the first COVID-19 case in Italy (21/02/2020) and the end of the lock-down (04/05/2020)?In order to answer that question we conducted a qualitative exploratory research thanks to which we were able to get in touch with the nursing homes and better understand the resources they used, the obstacles they encountered and some innovations they put in place.For the purpose of the study we collaborated with the Alberto Sordi Foundation. We involve 22 organisations coming from all the regions for two reasons: we were studying a healthcare system based on a regional model; the contagion spread differently in the various regions.The conclusions are focused on three elements that should regard the future perspectives on elderly care models: 1) care, which, seen as fundamental right underlying the recognition of citizenship; 2) an experimental territorial governance; 3) the implementation of a new service profession called care manager.